DEVELOPMENT OF WORDWALL LEARNING EVALUATION ON CONSUMER BEHAVIOR MATERIAL - Murdianningsih, Asri Rahayu; Faslah, Roni; Fidhyallah, Nadya Fadillah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This study aims to assess the validity of the development of wordwall-based learning evaluation in business communication subjects with consumer behavior material for class X retail business at Vocational High School Tamansiswa 1 Jakarta. This study uses Research and Development (RnD) using the ADDIE development model. Thus, the analysis, design, development, and implementation stages are the first stages carried out in the research and development of this learning evaluation. The results of this study are the results of the media expert validation analysis which gives a percentage of 84% in the very valid group. In addition, 80% of the results in the valid category come from the material expert validation analysis. Furthermore, based on the validation results by the teacher, the figure was 80%, which is also in the valid category. The results of the small group trial by students showed a figure of 82% which falls into the very valid category. This percentage shows the validity and feasibility of using wordwall-based learning evaluation as a learning assessment in the classroom.